MODAHA KAMBUNGU: PENINGKATAN KESADARAN MASYARAKAT DESA BUNUYO TERHADAP PENYEBARAN HOAX SEBAGAI TINDAK PIDANA MENJELANG PILKADA SERENTAK 2024 - Imran, Suwitno Y.; Hippy, Janwar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The negative impact of the spread of hoaxes in the face of general elections, including the regional head elections in Pohuwato Regency in 2024, is important to guard against the spread of false news so that horizontal conflicts do not occur between communities while creating a healthy democratic climate. Therefore, a series of service activities were carried out in solving the problem by setting a location in Bunuyo Village as one of the villages that will hold Pilkada in Pohuwato Regency. The community service activities were carried out in the form of zone mapping on the vulnerability of hoax distribution, legal counseling on the forms and dangers of hoax distribution, and Digital Literacy training as well as the formation of community groups that anticipate the spread of hoaxes. The final result of the implementation of this service is the knowledge of the potential of village areas that are vulnerable to the spread of hoaxes. thus, counseling efforts and digital literacy training are carried out, leading to the existence of community groups formed with the task of anticipating and counteracting hoax problems ahead of the Pilkada in order to create a conducive area and safe Pilkada.